The Rodent Pest Species Infesting Maize (Zea mays L) and Wheat (Triticum aestivum L) Farms at University of Eldoret, Uasin Gishu County, Kenya - Werunga , Mispah; Mwaniki , Dickson M.; Wanjala , Fredrick M. E. (African Journal of Education,Science and Technology (AJEST), 2023)
Rodents are pests of concern in Kenya, as they cause considerable damage to cereal during pre harvest and post-harvest period and therefore affecting food security by impacting on both food availability, quantity and quality. However, knowledge on rodent pests and cereal crops infested in Kenya is limited. The objectives of the research were to investigate the rodent pest species that infest maize and wheat farms, determine the rodent species, gender (males and females) and population distribution in maize and wheat farms at University of Eldoret. Two habitats (Maize and wheat farms) were selected for the study. Grids of 70mx70m crop cuttings were done in commercial fields of maize and wheat. The grid was subdivided into four quarters each with 4 Sherman’s live traps and 4 locally woven live traps, a total of 32 trapping points were established. Peanut butter and sun dried Omena (Rastrineobola argentea) was used as baits. Rodents captured were identified up to species level using keys for classifying rodents. The SPSS statistical package version 22.0 was used to analyze the data. Chi square test was used to compare the populations of myomorph rodents captured during the cropping period in both farms, independent sample t-test was used to compare the variation in infestation between the two habitats, gender and species distribution, Autoregressive Integrated Moving Average (ARIMA) [1, 1, 1] [2, 0, 0] Time series model was used to forecast the trend of rodent incidences. The results were presented in tables and figures. Three myomorph rodent species were recorded during the three-year study period. They included Mastomys natalensis (M. natalensis), Arvicanthis niloticus (A. niloticus) and Lemniscomys striatus (L. striatus). A total of 924 myomorph rodents were captured during study period with 50.97%, 19.48% and 29.54% captured in year one, two and three respectively. Mastomys natalensis represented the highest captures 60.61% followed by Arvicanthis niloticus 38.42% and then Lemniscomys striatus 0.97%. There was variation in infestation between the two fields with rodents showing preference to maize than wheat farms. There were more M. natalensis and A. niloticus in maize compared to wheat farms and L. striatus was a rare species during this study. There was a significant variation in infestation in year one (P =.001) and no significant variation in distribution of myomorph rodents in year two (P = .499) and year three (P = .127) cropping period. Species displayed variation in distribution with negative relationship in terms of species incidences and habitat in year two (t = -0.677; P =.499) and positive relationship (t = 1.529; P = .127) for year three. There was a significant difference in distribution of gender (males and females) in second year of study (t = -2.625, P = .009) and overall, no significant variation in distribution of gender (t = 0.525, P = .600) in the two habitats. ARIMA (1, 1, 1) model depicted that there was abundance of the rodent pests between the months of March and July, with decline in the months of November to January for the forecasted year with minimal variations. The findings (t = 3.523, P = .001) also revealed that there was a statistically significant difference in species distribution between the rodents in maize and wheat fields. In conclusion, the three myormoph rodent pests species distribution varied in maize and wheat farms and the population varied from year to year with higher incidences of pests in maize than wheat fields. Despite the varying numbers of either species in both maize and wheat, the types of species did not vary in both fields. There was no significant difference between gender (male and female) of rodent species in maize and wheat farms. The abundance could increase to cause loss and therefore needs to determine rodent pest control strategies to minimize the numbers and population of these rodent species in the study area and other regions that grow maize and wheat.